Tingkat serangan hama tongkol pada beberapa varietas jagung di Lampung - Imawati, Imawati; Fitriana, Yuyun; Swibawa, I Gede; Lestari, Puji; Susilo, Franciscus Xaverius; Hariri, Agus Muhammad (Universitas Lampung, 2025)
Maize is an important commodity as a source of food, feed and industry. The presence of pests can reduce productivity and cob quality. This study aims to determine the various types of pests that attack corn cobs and their level of attack on several varieties of corn. The survey was conducted in four districts of corn production centers in Lampung: East Lampung, South Lampung, Pesawaran, and Pringsewu. Two fields were taken from each district as sampling sites. Identification was conducted at the Plant Pest Science Laboratory, Faculty of Agriculture, University of Lampung. The results showed that aphids were the pest with the highest population density in Pringsewu, Pesawaran, and East Lampung Districts, which were 17.3 individuals per plot, 35.6 individuals per plot, and 23.8 individuals per plot, respectively. Powder beetles had the highest population density in South Lampung District at 15.1 individuals per plot. The highest damage intensity was found in Bisi 99 and Bisi 79 varieties caused by armyworms, which amounted to 4.18% and 4.30%.